Exacerbation of diclofenac-induced gastroenterohepatic damage by concomitant exposure to sodium fluoride in rats: protective role of luteolin (2020)
NSAID-induced gastrointestinal toxicity is associated with non-selective inhibition of cyclooxygenase (COX)-mediated synthesis of prostaglandins. Fluoride salts, known to stimulate COX-2 synthesis, have also been associated with gastrointestinal damage. The effects of fluoride treatment on NSAID toxicity are, however, yet to be clarified. This study examined the effect of sodium fluoride (NaF) on diclofenac (DIC)-induced gastroduodenal and hepatic toxicity in rats. In addition, the potential protective role of Luteolin (Lut), an antioxidant and anti-inflammatory flavonoid, in co-exposure to NaF and DIC was also investigated. Five groups of rats were treated thus: Group A (control): distilled water vehicle for 8 days; Group B: DIC (9 mg/kg) orally, twice daily from days 6 to 8; Group C: NaF (300 ppm) plus DIC for the final 3 days; Groups D and E: Luteolin at 100 mg/kg and 200 mg/kg, respectively, with concurrent NaF and DIC exposures. Rats co-treated with DIC and NaF exhibited the highest severity of dark watery diarrhea and gastroduodenal hemorrhages. NaF aggravated the DIC-induced increases in malondialde hyde (MDA), advanced oxidation protein products (AOPP), protein carbonyls (PC), H2O2, and nitric oxide, while inhibiting glutathione peroxidase (GPx) and glutathione S-transferase (GST) in all the tis sues. In contrast, Luteolin treatment significantly attenuated the gastroduodenal and hepatic damage caused by NaF and DIC co-administration by suppressing oxidative damage and lesions in the tissues. These results show, for the first time, that NaF may enhance diclofenac-induced gastrointestinal toxicity and also suggest that Luteolin may be a promising lead for the treatment of drug-induced gastroenteropathy.